IMPROVING THE MODEL FOR DEVELOPING STUDENTS' ARTISTIC TASTE AND AESTHETIC THINKING THROUGH THE STUDY OF CREATIVE WORKS - Temirov Murodjon Anvarovich (Scholar Express Journal, 2025)
The purpose of this study is to develop an effective model for developing students' artistic taste and aesthetic thinking through the study of creative works. During their studies, students should acquire not only academic knowledge but also aesthetic and artistic skills. This goal is achieved through an in-depth analysis of works of art and an understanding of their aesthetic value.
Keywords: artistic taste; aesthetic thinking; creative activity